Drones on the horizon: Transforming Africa’s agriculture - High-Level African Panel on Emerging Technologies (NEPAD Planning and Coordinating Agency, 2019)
This report provides a contextualized review of drones as a vital precision agriculture-enabling technology and its range of relevant uses for providing detailed and on-demand data in order to enhance decision-making by farmers and hence facilitate much needed support.